Kesehatan Mental Penggemar dalam Lagu My Treasure - Mulyadi, Iffa Salsabila; Soedarsono, Dewi K (UMSU, 2025)
Music is a powerful communication tool in health communication that can affect the physical, mental and emotional aspects of individuals. Music is also used as a means to deliver health messages. Music has various genres that continue to grow ranging from Pop, Hip Hop, RB, Reggae, Jazz, and others. These music genres then develop into sub-genres of music, one of which is K-Pop or Korean Pop. Indonesia is the third most streamed country in K-Pop music. According to a report from Twitter, Indonesia is the country with the most K-Pop fans in the world. The K-Pop phenomenon in Indonesia is very rampant, especially among young people, especially generation Z. One of the boy groups from South Korea that is currently actively working is Treasure. Treasure specifically released several songs that contain support for fans, one of which is the song